Fasad Dalam Alquran: Analisis Semiotika Roland Barthes - Alby Alqowi, Yahya Alby Alqowi; Rawzalgina, Arthi Amalia (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
In the modern era marked by ecological crisis and declining human values, the concept of fasad in the Qur'an needs to be re-considered in contemporary Islamic discourse. This study aims to examine the depth of the meaning of fasād in Surah Al-Baqarah (2:11) through Roland Barthes' semiotic theory approach. By tracing the layers of denotative, connotative, and mythological meanings, this approach reveals that the Qur'anic discourse on damage is full of complex and ideological meanings. This study uses a qualitative method based on literature study and a thematic interpretation approach (tafsir maudhu'i), by examining verses that discuss damage in various social, ecological, and spiritual contexts. The results of the study show that fasād, especially in QS. Al-Baqarah: 11, does not only refer to physical or material destruction, but also to deep moral and ideological damage such as hypocrisy, social disintegration, and ethical manipulation that are often disguised through the rhetoric of improvement (iṣlaḥ). Through Barthes' semiotic framework, the facade appears to function as a myth of legitimacy of power, which wraps the practice of exploiting resources and values ​​in a constructive intention. This finding confirms that semiotic theory can enrich the treasury of Qur'anic interpretation by opening up critical interpretative space, and positioning the Qur'an as a living ethical reference that is relevant to the complexity of the modern era.